Trend of Creative Thinking Researches in Chemistry Education from Research Design to Data Analysis: A Literature Review - Baiq Miftah Azumi; Siti Aisyah; Eli Rohaeti (Postgraduate, University of Mataram, 2024)
Creative thinking is a skill needed to meet the demands of the 21st century. The complexity of learning chemistry requires students to have creative thinking skills to solve the problems they will face. This research aims to gather information about various studies that discuss creative thinking skills. The research method employed in this study involves a literature review with content analysis of several articles, focusing on the entirety of articles published from 2015 to 2024, all of which are indexed by Scopus. A total of 15 articles were reviewed after a screening process according to the inclusion criteria. The results showed that among these publications, the predominant research design was quantitative. The majority of the research subjects were undergraduate students, with biochemistry being the most frequently observed topic. The problem-based learning (PBL) method was the most commonly used, with tests, observation sheets, and interview sheets as the most common data collection instruments, along with t-tests for data analysis.